Elevational variation of reproductive traits in five Pardosa (Lycosidae) species - Hein, Nils; Feilhauer, Hannes; Löffler, Jörg; Finch, Oliver (Arctic, Antarctic, and Alpine Research, 2015)
Differentiations in reproductive traits along climatic gradients can be substantial for a species to spread along a wide spatial range. We compared the reproductive effort allocated to first egg sacs of five species of the genus Pardosa: P. palustris (Linnaeus 1758), P. amentata (Clerck 1757), P. lugubris (Walckenaer 1802), P. hyperborea (Thorell 1872), and P. riparia (C. L. Koch 1833) along three elevation transects in central Norway. We tested whether population differences are consistent among the three transects, respectively along the elevational gradient. We assumed that the harsh environments of alpine areas would lead to adaptations in reproductive traits resulting in larger eggs but smaller clutches at higher elevations. The results show that female size and egg number were positively correlated among all species. However, no clear elevation-related trend was found. Other traits did not change consistently between species and along the elevational gradient. We assume that local microclimatic impacts on spider fitness are a crucial but poorly understood factor. Without further knowledge about adaptation and phenotypic plasticity in ectotherms, modeling of possible future reproduction biology might remain flawed.